Distributing Zakat al-Fitr to Quranic Teachers and Midwives from an Islamic Law Perspective:: Case Study in Tamangapa Village, Pangkep Regency, South Sulawesi - Baedah, Said Syaripuddin Abu; Syahid , Akhmad; Hasibuddin , M.; Firawati , Firawati (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2026)
This paper aims to analyze the tradition of distributing zakat al-fitr to Quranic teachers and midwives from an Islamic perspective in Tamangapa Village, Makassar City. By conducting a descriptive field study, obtained through observation, interviews, and documentation, it is possible to describe the social reality of the Tamangapa Village community, Makassar City, in distributing their zakat al-fitr to midwives and Quranic teachers. The results of the study indicate that in general, Tamangapa Village residents who use the services of midwives in addition to midwives distribute their children's zakat al-fitr to them from infancy until the age of three. Furthermore, if the child is four years old or older and has been registered at the Quranic Education Center (TPA), the distribution of zakat al-fitr is transferred to the Quranic teacher until he or she has successfully completed the Quran (approximately three years). The community's habit of distributing zakat al-fitr only to these two parties is due to following their parents' traditions. However, Islamic law does not permit the distribution of zakat al-fitr solely based on